Model Analysis Faktor Sebaran Data Curah Hujan Tahunan - Riki Chandra Wijaya; Umboro Lasminto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
Rainfall occurs in Watershed (DAS) has a special relationship. Data distribution from measuring devices at several locations in the watershed is predicted to have patterns and close relationships. To know this we need a model to be able to show a relationship between measured rainfall data. This research, a factor analysis model is performed to calculate how much the relationship between rainfall data in the watershed and to determine the shape of rainfall distribution patterns that occur. Based on the calculation results, it is known that pattern of rainfall data distribution from 6 rain stations in Bengawan Solo watershed, namely doplang, randu, menden, kedung, japah, and sambong in 1998 has the same distribution pattern. However, the amount of rain height is different. In addition, the maximum Pearson correlation coefficient is 0.536 at Menden-Randu station. While the minimum Pearson correlation value for the Menden-Sambong station is 0.012. This difference is influenced by the distance between Menden-Randu and Menden-Sambong stations. Based on calculations on the factor analysis model, there are two factors that affect directly between these stations. Factor 1 has coefficient value 0.5. Based on calculations show that rainfall that occurs in each region does not have a strong relationship between one another, but the occurrence of rain that occurs has the same distribution pattern. From this, it provides information that th e pattern of rainfall distribution each year is the same due to the occurrence of rain following climate patterns in global area coverage.